Intracranial haemorrhage in children with inherited bleeding disorders in the UK 2003‐2015: A national cohort study. Issue 4 (10th April 2018) - Chalmers, E. A.; Alamelu, J.; Collins, P. W.; Mathias, M.; Payne, J.; Richards, M.; Tunstall, O.; Williams, M.; Palmer, B.; Mumford, A.
Abstract : Introduction: Intracranial haemorrhage in children with inherited bleeding disorders is a potentially life‐threatening complication and presents a significant therapeutic challenge. Aim: To define the characteristics, management and outcomes of intracranial haemorrhage presenting in UK children ≤16 years of age with inherited bleeding disorders from 2003 to 2015. Method: Retrospective analysis of children treated at UK haemophilia centres. Results: Of 66 children presenting with Intracranial haemorrhage (ICH), 82% had haemophilia A or B, 3% VWD and 15% a rare IBD. The IBD was a severe phenotype in 91%. The rates of ICH were 6.4 and 4.2 per 1000 patient years for haemophilia A and B, respectively. Median age at presentation was 4 months (33% neonates; 91% children <2 years of age). In neonates, delivery was spontaneous vaginal (SV) in 11, instrumental in 6, caesarean in 4 and unknown in 1. In children with haemophilia, the risk of ICH after instrumental delivery was 10.6 times greater than after SV delivery. Trauma was more common in children >2 years (67%) than in children 1 month to 2 years (18%; P = .027). Prior to ICH, only 4.5% of children were on prophylaxis. 6% of haemophiliacs had an inhibitor. The median duration of initial replacement therapy was 15 days. Mortality was 13.5%. Neurological sequelae occurred in 39% of survivors, being more common following intracerebral bleeding. In haemophilia survivors, 52% subsequently developed a FVIII inhibitor. Conclusion: Intracranial haemorrhage occurs most frequently in children with severe IBDs, during the first 2 years of life and in children not receiving prophylaxis. Intracranial haemorrhage often occurs without documented trauma.